Cigarette purchase patterns in four countries and the relationship with cessation: findings from the International Tobacco Control (ITC) Four Country Survey. (5th June 2006) - Hyland, A; Laux, F L; Higbee, C; Hastings, G; Ross, H; Chaloupka, F J; Fong, G T; Cummings, K M
Abstract : Background: Higher cigarette prices result in decreased cigarette consumption, but some smokers may seek lower-taxed cigarette sources. This price avoidance behaviour likely dampens the health impact of higher cigarette prices although it has not been thoroughly studied. Objective: To describe the characteristics of smokers who purchase low/untaxed cigarettes and to examine how this behaviour is associated with subsequent changes in smoking behaviours. Methods: Telephone survey data from 8930 smokers from the International Tobacco Control (ITC) Four Country Survey (ITC-4) were used to assess cigarette purchase patterns and smoking behaviours in Wave 1 conducted from October to December 2002 and subsequently followed seven months later in Wave 2. Respondents' smoking status, attempts to quit, amount smoked, and cigarette purchase patterns were assessed in both waves. Results: Rates of purchase from a low/untaxed source at the respondents' last cigarette purchase differed notably between countries at Wave 1, from less than 1% in Australia to 15% in the United Kingdom. In the UK, but not the other countries, this increased significantly to 20% at Wave 2. Smokers who were older, white/English speakers, had higher incomes, and had higher levels of education were more likely to report purchasing cigarettes from a low/untaxed source on their last purchase. Those who reported purchasing from a low/untaxed source on their last purchase at Wave 1 were less likely to have tried to quit smoking quit smoking by Wave 2 (relative risk 0.70, p < 0.01), while no overall significant association with smoking cessation was observed. Conclusion: Data from this study indicate that there are lower levels of making a quit attempt among purchasers of low/untaxed cigarettes compared to purchasers of full-priced cigarettes. The availability of low/untaxed cigarettes may mitigate the influence of increases in cigarette prices.